2012
DOI: 10.4137/cmt.s7298
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Fentanyl for Breakthrough Pain Control

Abstract: Breakthrough pain (BTP) is experienced by approximately 65% of children and adults with chronic pain. Undiagnosed or untreated BTP produces negative emotional, physical, and economic consequences. BTP episodes have a rapid onset and short duration. Short acting oral opioids are the cornerstone of BTP management. Oral medications available to treat BTP episodes like immediaterelease morphine or oxycodone have a delayed onset of action so that there is a mismatch between the episode of BTP and the effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…(12) Fentanyl also has a rapid onset of action (within 6-8 minutes following intranasal administration) due to its high lipid solubility. (13) Studies conducted in prehospital settings have shown that intranasal fentanyl is as effective an analgesic as intravenous morphine in adult (14) and paediatric patients. (15) Although the evidence regarding the use of intranasal fentanyl in EDs is limited, the few published studies show promising results.…”
Section: Introductionmentioning
confidence: 99%
“…(12) Fentanyl also has a rapid onset of action (within 6-8 minutes following intranasal administration) due to its high lipid solubility. (13) Studies conducted in prehospital settings have shown that intranasal fentanyl is as effective an analgesic as intravenous morphine in adult (14) and paediatric patients. (15) Although the evidence regarding the use of intranasal fentanyl in EDs is limited, the few published studies show promising results.…”
Section: Introductionmentioning
confidence: 99%